Language Teaching for a Sustainable Future: Integrating Sustainability in ELT - Dewi Sari Wahyuni; T. Sy Eiva Fatdha (Journal of Social Work and Science Education, 2026)
This study investigates how sustainability principles can be integrated into English Language Teaching (ELT) to enhance educational quality and foster global citizenship. Adopting a qualitative integrative literature review design, we synthesized findings from 35 publications (2013–2025). It includes two recent systematic reviews and a case study to identify pedagogical strategies, challenges, and outcomes of incorporating sustainability in ELT. The results reveal a range of practical approaches, including Content and Language Integrated Learning (CLIL) curricula, project-based learning centered on the Sustainable Development Goals (SDGs), eco-critical language awareness activities, and targeted teacher training. These approaches were found to enhance language proficiency while increasing learners’ sustainability awareness and engagement. However, significant challenges remain, notably a lack of appropriate teaching resources and teacher preparedness, as well as misalignment between sustainability topics and traditional language curriculum goals. As a novel contribution, this study proposes a synthesized framework for embedding sustainability into ELT, along with evidence-based recommendations to overcome implementation barriers. In practical terms, integrating sustainability content and practices in ELT engages students with real-world issues, fostering critical thinking and global citizenship skills alongside language development. The study’s findings offer new insights by explicitly linking ELT to Education for Sustainable Development (ESD) goals and provide ELT professionals with concrete strategies to help build a more sustainable future through language education.